Sunitinib for metastatic renal cell cancer patients: observational study highlighting the risk of important drug–drug interactions. (13th January 2014) - Kruse, V.; Somers, A.; Van Bortel, L.; De Both, A.; Van Belle, S.; Rottey, S.
Summary What is known and objective Sunitinib, a CYP3A4 substrate, is standard of care treatment in metastatic renal cell carcinoma (mRCC) and is administered orally as a single dose of 50 mg, in a 4 weeks on/2 weeks off regimen. Frequently, dose reduction is necessary because of toxicity, as is the association of comedication to treat side effects. In addition, existing comorbidities in these patients necessitate the intake of various classes of chronic medication. Only limited data are available on the risk of drug–drug interactions (DDI). The objective of our paper was to evaluate prescribed dose, comedication, risk of drug–drug interactions and outcome among patients with mRCC treated with sunitinib. Methods A single‐centre, retrospective analysis was performed for patients with mRCC treated with sunitinib. The drug interaction databases 'Clinical Pharmacology'© and 'Lexicomp'© were used to screen for possible interactions. Results and discussion The hospital files of 36 patients with mRCC were evaluated. Twenty‐two patients received sunitinib as first‐line treatment. Progression‐free survival (PFS) in this first‐line group was longer for patients that started with full‐dose sunitinib (21·1 months; n = 12) than for patients started on reduced dose (3·5 months; n = 10). In the whole group of 36 patients, an average of 6·8 comedications was taken. Possible pharmacodynamic drug–drug interactions were most frequently found (47%) and reported as major interactions (QT prolongation). Risk of pharmacokinetic interactions due to co‐administration of CYP inhibitors, CYP inducers, CYP substrates and PgP substrates was reported for 8%, 11%, 53% and 19%, respectively. These interactions were reported as major or moderate. What is new and conclusion Patients with mRCC under treatment with sunitinib at a reduced starting dose had a decreased PFS compared with patients started with full‐dose sunitinib. Due to adverse drug reactions and comorbidity, patients under sunitinib, a CYP3A4 substrate, took an average of 6·8 comedications provoking an important risk of major‐to‐moderate drug–drug interactions. With the help of a multidisciplinary team, avoidance of drug–drug interactions could be obtained. Moreover, serial ECG monitoring is recommended for patients at high risk of QT prolongation.